Search for charged Higgs bosons decaying into a top and a bottom quark in the all-jet final state of pp collisions at √s = 13 TeV - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich (2020, 2020)
Title screen